The removal of black ink via Emericella quadrilineata as a green alternative technique to recycling ink waste papers - Mari Sumayli; Abdullah Mashraqi; A. El-Shabasy; Ugur Azizoglu; Sally A. Ali (PLoS ONE, 2025)
In order to fight deforestation, biological methods of recycling printed waste papers must be used. In addition to identifying and isolating A. quadrilineatus, the current study attempts to ascertain the best physiological conditions and mechanisms underlying this species’ ability to deink. Five isolates such as Cladosporium sp., Aspergillus sp., Fusarium sp., Penicillium sp., and Rhizopus sp. isolated from soil containing ink remains using Bushnell and Hass media carried out the deinking tests. SEM, FT-IR, the molecular method, and factors affecting ink eradication were all carried out. The deinking of ink-loaded filter paper, Langmuir and Freundlich adsorption isotherms, and A. quadrilineatus enzyme activities were also investigated in this work. Ninety per percentage of the black ink was removed by A. quadrilineatus. Six days later, under ideal conditions (pH 6, temperature 30°C, initial ink concentrations of 20,000 mg L ⁻ ¹, and inoculum dose of three fungal discs), the optimal deinking percentage from solution through a culture of A. quadrilineatus reached up to 97%. The deinking mechanism of A. quadrilineatus was shown by SEM and FT-IR studies. A good level of agreement between the Langmuir adsorption isotherm model and the adsorption process was shown by the Freundlich and Langmuir adsorption isotherms. Otherwise, on agar plates, A. quadrilineatus demonstrated its capacity to manufacture the enzymes lipase and xylanase. Overall, the results indicated that A. quadrilineatus may open up new possibilities for recycling printed waste papers.